Effect of preinitiated glucose-insulin-potassium strategy for patients with undergoing planned percutaneous coronary intervention: a systematic review and meta-analysis - Feng Xu; Chuanbao Li; Huiruo Liu; Rugang Liu; Zeyu Yang (BMJ Open, 2023)
Objectives Whether the glucose-insulin-potassium (GIK) should be used as an adjuvant therapy for ischaemic myocardial disease remains controversial nowadays reperfusion era. This meta-analysis aimed to assess the effects of preinitiated GIK for patients undergoing planned percutaneous coronary intervention (PCI).Design Systematic review and meta-analysis.Data sources PubMed, Web of science, MEDLINE, Embase, Cochrane Library and ClinicalTrials.gov were searched through 27 November 2022.Eligibility criteria Only randomised controlled trials involving participants preinitiated with GIK or placebo before planned PCI were included.Data extraction and synthesis Two independent reviewers used standardised methods to search, screen and code included trials. Risk of bias was assessed with the Cochrane tool. Pooled analysis was conducted using random or effects models according to the heterogeneity. Subgroup analyses were carried out for dosage of GIK and if with ongoing myocardial ischaemia.Results 13 randomised controlled trials (RCTs) including 3754 participants were evaluated. We found patients preconditioned with GIK before PCI showed a significant increase in Thrombolysis in Myocardial Infarction 3 flow events after angioplasty (OR 1.59, 95% CI 1.03 to 2.46, p=0.04), also revealed improved in-hospital left ventricular ejection fraction (weighed mean difference, WMD 1.62, 95% CI 0.21 to 3.03, p=0.02) and myocardial salvage index (WMD 0.09, 95% CI 0.01 to 0.16, p=0.03). Nevertheless, no benefit was observed in all-cause mortality neither on 30-day (OR 0.81, 95% CI 0.59 to 1.11, p=0.18) nor 6 months (OR 1.02, 95% CI 0.42 to 2.46, p=0.97). Furthermore, GIK intervention was associated with higher occurrences of complications such as phlebitis (OR 10.13, 95% CI 1.74 to 59.00, p=0.01) and hypoglycaemia (OR 10.43, 95% CI 1.32 to 82.29, p=0.03), but not hyperkalaemia (OR 9.36, 95% CI 0.50 to 175.27, p=0.13), liquid overload (OR 1.02, 95% CI 0.25 to 4.13, p=0.98) or in-hospital heart failure (OR 0.42, 95% CI 0.06 to 2.96, p=0.39).Conclusions Our study shows preconditioning GIK exhibits myocardial reperfusion and cardiac function benefits for patients planning to receive PCI intervention, while also some complications such as phlebitis and hypoglycaemia accompany.PROSPERO registration number CRD42022326334.